Pengaruh Pengetahuan Investasi, Persepsi Risiko dan Pengelolaan Keuangan terhadap Minat Investasi : (Studi Kasus pada Mahasiswa Universitas Muhammadiyah Jember) - Dwiki Auly Qaristey; Feti Fatimah; Ahmad Izzudin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine how much influence investment knowledge, risk perception, and financial management skills have on students' interest in investing at the University of Muhammadiyah Jember. In the midst of the development of the digital era, investment has become an important issue that needs to be understood by the younger generation, especially students as future investors. Therefore, this study is important to identify factors that can encourage their interest in investing. The method used in this study is quantitative with a survey approach. Data were obtained by distributing questionnaires to students who have an interest or initial understanding of investment. The research sample was 100 students majoring in management at the University of Muhammadiyah Jember using the purposive sampling method. Data analysis was carried out using multiple linear regression with the help of SPSS software. The research findings show that investment knowledge and financial management significantly and positively influence students' interest in investing. Meanwhile, risk perception has a negative but still significant effect on investment interest. This means that the better a person's understanding of investment and ability to manage finances, the higher the interest in investing. Conversely, if the risk is perceived as too high, the interest in investing will decrease. This research contributes to educational institutions and financial institutions to improve financial literacy and investment among students in order to create a younger generation that is more financially literate and ready to face future economic challenges.